Peran Akuntansi Hijau dalam Keberlanjutan Perusahaan di Indonesia - Ade Gunawan; Achmad Tubagus Surur; Muhammad Nasrullah; Adinda Umul Fadzila (Jurnal Akuntansi dan Audit Syariah)
This research explores the role of green accounting in supporting the sustainability of companies in Indonesia. As the environmental concerns become increasingly pressing, companies are called upon to adopt sustainable practices that align with both national and international regulations. Green accounting, which integrates environmental costs into financial reporting, plays a crucial role in helping businesses manage environmental impacts while also contributing to their long-term sustainability. The study employs a literature review method to examine how green accounting practices are being implemented in Indonesia, the challenges faced by companies, and the regulatory frameworks that influence these practices. The results indicate that while green accounting is gaining traction, there are still barriers related to the measurement of environmental costs and benefits, as well as inconsistent regulatory enforcement. Companies that adopt green accounting practices are shown to have better stakeholder relations and are more competitive in the market. This research suggests that further strengthening of regulations and education on green accounting is essential for fostering sustainable business practices.